Automated reasoning with analytic tableaux and related methods : 26th International Conference, TABLEAUX 2017, Brasília, Brazil, September 25-28, 2017, Proceedings /: 26th International Conference, TABLEAUX 2017, Brasília, Brazil, September 25-28, 2017, Proceedings. (2017) - Unknown
No abstract available